2008
DOI: 10.1007/s10953-008-9327-6
|View full text |Cite
|
Sign up to set email alerts
|

Acetohydroxamatoiron(III) Complexes: Thermodynamics of Formation and Temperature Dependent Speciation

Abstract: 1 Acetohydroxamatoiron (III) complexes Andrieux et al. AbstractStudies of the thermodynamics of formation of the acetohydroxamatoiron(III) complexes were carried out in acidic media at temperatures ranging from 293 to 323 K. Through the isolation of the unique UV -visible spectra of all three complexes, it was possible to determine their formation constants and deduce enthalpies and entropies of formation as well as their molar absorptivities. The enthalpies of formation of the mono-, bis-and trisacetohydroxam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In order to obtain absorbance spectra useful for the determination of stability constants in SQUAD, distinct concentration ratio ranges of Fe(III) and AHA were determined from the Hyperquad Simulation and Speciation (HySS) program (21) and previous literature (16,17). Critically assessed equilibrium data indicated that the formation of Fe(OH) 2þ only becomes significant above pH 2.17 (17,22,23). Therefore, the hydrolysis of Fe(III) was not of consideration in HySS, as the pH of all solutions was 1 and the concentration of the ferric ion was low.…”
Section: Results and Discussion Fe(iii) Acetohydroxamate Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to obtain absorbance spectra useful for the determination of stability constants in SQUAD, distinct concentration ratio ranges of Fe(III) and AHA were determined from the Hyperquad Simulation and Speciation (HySS) program (21) and previous literature (16,17). Critically assessed equilibrium data indicated that the formation of Fe(OH) 2þ only becomes significant above pH 2.17 (17,22,23). Therefore, the hydrolysis of Fe(III) was not of consideration in HySS, as the pH of all solutions was 1 and the concentration of the ferric ion was low.…”
Section: Results and Discussion Fe(iii) Acetohydroxamate Complexesmentioning
confidence: 99%
“…Acetohydroxamic acid forms strong complexes with iron(III) which can be monitored by observing the intense color of the complex formation. Conditional stability constants of Fe(AHA) 2þ , FeðAHAÞ þ 2 , and Fe(AHA) 3 in 0.1 mol Á L À1 NO À 3 and pH 1.0 at 25 C are reported and compared with previously reported values (16,17).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…To determine the origin of this colouration, the working solution was sampled after electrochemical 8 scanning, diluted and analysed using UV-vis spectrophotometry (not shown). Comparison with absorbance peak values for acetohydroxamatoiron(III) complexes reported by Andrieux et al [14], revealed the presence of the monoacetohydroxamatoiron(III) complex suggesting that electrogenerated Fe(III) is sequestered from the electrode surface in this form.…”
Section: Microgravimetric Studies Of Ss2343 Dissolution In the Presenmentioning
confidence: 51%
“…The stock solution was kept refrigerated up to a maximum of five days and colourmetrically checked daily for AHA degradation using UV-vis spectrophotometry [14].…”
Section: Aha Preparationmentioning
confidence: 99%